Analysis of Character Education As an Effort to Realize the Profile of Pancasila Students in the 5.0 Era - Ibrila Hind Aqiila; Feri Tirtoni (STAI Hubbulwathan Duri, 2023)
The study was conducted to analyze the character education of fourth-grade students in a public elementary school in Keboharan, Sidoarjo. In the 5.0 era, emphasizing an easy, fast, and digital media-centred lifestyle. The issues raised in this research are: how to instill discipline in students, how teachers introduce students to digital media, and how to regulate their use. The sample was taken using Purposive Sampling, where the researcher selected samples based on specific criteria among the respondents. In this research, the class teacher was the sample. The research method used was qualitative. The results divided character education into four indicators: time management, obedience to rules, discipline in completing tasks, and discipline in speaking. This was done in the elementary school by providing moral messages during lessons, leadership training for each student, and appreciation for what the students have achieved. In the 5.0 era, teachers teach and introduce students to digital media while also setting limits. The results also prove that character education is essential in the development and life of students, as well as discipline in using digital media among students.